2016
DOI: 10.2147/ott.s121619
|View full text |Cite
|
Sign up to set email alerts
|

A novel synthetic Asiatic acid derivative induces apoptosis and inhibits proliferation and mobility of gastric cancer cells by suppressing STAT3 signaling pathway

Abstract: Activation of the transcription factor, signal transducers and activators of transcription 3 (STAT3), has been linked to the proliferation and migration of a variety of human cancer cells. These actions occur via the upregulation or downregulation of cell survival and tumor suppressor genes, respectively. Importantly, agents that can suppress STAT3 activation have the potential for use in the prevention and treatment of various cancers. In this study, an Asiatic acid (AA) derivative, N-(2α,3β,23-acetoxyurs-12-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…It has been proposed that Asiatic acid has various pharmacological activities such as anti-inflammatory and antioxidant, as well as the potent anti-hypertensive, neuro and cardio-protective, antimicrobial, and antitumor activities [5]. Many studies had proved the anti-cancer effects in vitro or in vivo of AA in breast cancer, ovary cancer, colon cancer, gastric cancer, cholangiocarcinoma, glioblastoma, lung cancer, lymphoma, and melanoma [6,[11][12][13][14][15][16][17][18]. Our study corresponds with these researches and revealed the anti-cancer effect of AA in both dose and time dependent manners in cisplatin-resistance NPC cell lines (Figure 1b).…”
Section: Discussionmentioning
confidence: 99%
“…It has been proposed that Asiatic acid has various pharmacological activities such as anti-inflammatory and antioxidant, as well as the potent anti-hypertensive, neuro and cardio-protective, antimicrobial, and antitumor activities [5]. Many studies had proved the anti-cancer effects in vitro or in vivo of AA in breast cancer, ovary cancer, colon cancer, gastric cancer, cholangiocarcinoma, glioblastoma, lung cancer, lymphoma, and melanoma [6,[11][12][13][14][15][16][17][18]. Our study corresponds with these researches and revealed the anti-cancer effect of AA in both dose and time dependent manners in cisplatin-resistance NPC cell lines (Figure 1b).…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that STAT3 protein binds to a highaffinity binding site in the promoter region of the MMP2 gene, which upregulates MMP2 expression. Inhibition of STAT3 inhibits its target gene MMP2 and inhibits tumor cell invasion (33). In malignant tumors, E-cadherin, an epithelial marker, is downregulated, and vimentin, an interstitial marker, is upregulated; moreover, cell adhesion is decreased, migration is enhanced, and tumor cells are more susceptible to invasion and metastasis (34).…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that VGLL4 may interact with STAT3, and further CoIP experiments confirmed that VGLL4 has a protein–protein interaction with STAT3. It has been reported that MMP2, MMP-9, Cyclin D1, Cyclin E1, and Bcl-2 are downstream of STAT3 transcriptional regulation 3840 , and STAT3 is primarily activated by its protein phosphorylation and then activates downstream transcription 33 . By inhibiting and overexpressing VGLL4, we found that phospho-STAT3, Cyclin D1 and Bcl-2, downstream targets of STAT3, were elevated and inhibited, respectively.…”
Section: Discussionmentioning
confidence: 99%